Profile of the University Professor of the National University of San Marcos and its Rertinence with the Current Demands: School Professional of Library and Information Science - Estrada Cuzcano, Alonso (2018)
This paper intends to make a theoretical and reflexive collection about the professional profile of the university professor, also an analysis of the competences that this profile is required to meet the needs of society today, taking into account the technological changes and the New demands of the labor market, concluding that this profile must be constantly updated to guarantee generations of qualified professionals with values that meet these requirements. Finally, the profile of the teachers of the Professional School of Library and Information Science is analyzed, identifying their knowledge, skills and professional experience.